The Relationship Between Competency Framework and Research Performance: An Empirical Study in The Public Research Institutes in Vietnam - Tran Quang Huy; Hoang Minh; Tu Thao Huong Giang (STI Policy and Management Journal, 2022)
Competency framework has been studied widely for human resource development in organizations, but there are a few publications about researcher competency-based development in public research institutes. Therefore, the purpose of this paper is to investigate the relationship between competency framework and research performance in public research institutes to promote research career development in Vietnam. Data collected from 600 researchers in public research institutes used for analyses. Confirmatory factor analysis technique (CFA) and hierarchical multiple regression were applied to test the relationship between competency framework and research performance. The results provide supports for the view that competency framework positively affects research performance and task frequency positively moderates the relationship between competency framework and research performance in public research institutes. This paper explores the concept of competency framework for researchers in the public research institute context and clarifies its affect to the development of science, technology and innnovation in Vietnam. Keywords: Competency framework, public research institute, technical competency, research performance, Vietnam.